2022
DOI: 10.3389/fimmu.2022.966766
|View full text |Cite
|
Sign up to set email alerts
|

Anti-IL-6 therapies in central nervous system inflammatory demyelinating diseases

Abstract: Current treatments for central nervous system (CNS) inflammatory demyelinating diseases (IDDs) include corticosteroids, plasma exchange, intravenous immunoglobulin, and immunosuppressant drugs. However, some patients do not respond well to traditional therapies. In recent years, novel drugs, such as monoclonal antibodies, targeting the complement component C5, CD19 on B cells, and the interleukin-6 (IL-6) receptor, have been used for the treatment of patients with refractory CNS IDDs. Among these, tocilizumab … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 94 publications
0
1
0
Order By: Relevance
“…Various treatment options are available, including corticosteroids, TPE, IVIG, and immunosuppressant drugs. Treatment choice depends on the pathophysiology of the specific type of autoimmune encephalitis and the patients’ comorbidity 26 , 42 . A recent study concluded that more aggressive treatment regimens in autoimmune encephalitis patients improved the 2-year outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Various treatment options are available, including corticosteroids, TPE, IVIG, and immunosuppressant drugs. Treatment choice depends on the pathophysiology of the specific type of autoimmune encephalitis and the patients’ comorbidity 26 , 42 . A recent study concluded that more aggressive treatment regimens in autoimmune encephalitis patients improved the 2-year outcome.…”
Section: Discussionmentioning
confidence: 99%